2020
DOI: 10.1038/s42255-020-00276-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pyruvate carrier abundance mediates pathological cardiac hypertrophy

Abstract: Cardiomyocytes rely on metabolic substrates, not only to fuel cardiac output, but also for growth and remodelling during stress. Here we show that mitochondrial pyruvate carrier (MPC) abundance mediates pathological cardiac hypertrophy. MPC abundance was reduced in failing hypertrophic human hearts, as well as in the myocardium of mice induced to fail by angiotensin II or through transverse aortic constriction. Constitutive knockout of cardiomyocyte MPC1/2 in mice resulted in cardiac hypertrophy and reduced su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 33 publications
12
90
1
Order By: Relevance
“…Reductions in glucose oxidation may lead to systolic dysfunction because mice with a cardiac-specific mitochondrial pyruvate carrier subunit 1 deficiency exhibit impaired myocardial glucose oxidation rates, which leads to a marked decline in LVEF by $8 months of age (Zhang et al, 2020). Similarly, another study using the same mice also reported a significant decline in LVEF, but nearly all mice died of cardiac failure by $20 weeks of age (Fernandez-Caggiano et al, 2020). With regard to FoxO1, findings in 8-month-old db/db mice with a cardiac-specific FoxO1 deficiency have demonstrated alleviation of the decline in systolic functional parameters (LVEF and LVFS), although glucose oxidation was not assessed in this particular study (Qi et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Reductions in glucose oxidation may lead to systolic dysfunction because mice with a cardiac-specific mitochondrial pyruvate carrier subunit 1 deficiency exhibit impaired myocardial glucose oxidation rates, which leads to a marked decline in LVEF by $8 months of age (Zhang et al, 2020). Similarly, another study using the same mice also reported a significant decline in LVEF, but nearly all mice died of cardiac failure by $20 weeks of age (Fernandez-Caggiano et al, 2020). With regard to FoxO1, findings in 8-month-old db/db mice with a cardiac-specific FoxO1 deficiency have demonstrated alleviation of the decline in systolic functional parameters (LVEF and LVFS), although glucose oxidation was not assessed in this particular study (Qi et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Within CMs, mitochondria are one of the most important organelles. Mitochondria are involved in almost all the major biological process of CMs, including supporting cellular morphology, ATP production through the electron transport chain (ETC), regulation of intracellular calcium ion signaling, and balance of reactive oxygen species (ROS) levels (Huss and Kelly, 2005;Koo and Guan, 2018;Fernandez-Caggiano et al, 2020). The mitochondria occupy a large fraction of CM cell volume (35-40%) and supply more than 90% energy of the cells' energy requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many would argue that metabolic perturbations precede functional changes in many examples of cardiac malfunction. A striking example is provided by recent work showing that levels of the mitochondrial pyruvate carrier mediates pathological cardiac hypertrophy in human heart, and mouse knockout of cardiomyocyte mitochondrial pyruvate carriers resulted in cardiac hypertrophy and reduced survival ( Fernandez-Caggiano et al, 2020 ). Hence, we focus the remainder of this review on cardiac metabolism and substrate use as our thesis is that alterations in metabolism and substrate use may be key aetiological factors in the development of DCM.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, glucose is rapidly converted to glucose-6-phosphate and metabolised to pyruvate in the cytosol and then enters the TCA cycle. Reduced expression of the mitochondrial pyruvate carrier protein is associated with cardiac hypertrophy in human heart ( Fernandez-Caggiano et al, 2020 ). Hence, cardiomyocyte metabolism is considered to be highly adaptive and tightly regulated by hormonal and contraction signals, coupling fuel use with available substrate and metabolic need.…”
Section: Resultsmentioning
confidence: 99%